Mapping global research on shadow education: Trends and future agenda - Zalik Nuryana; Wenbin Xu; Shiqi Lu; Zaidatun Tasir; Suyadi Suyadi (Institute of Advanced Engineering and Science, 2023)
This study aimed to analyze bibliographies of journals, authors, and research topics on shadow education using the Scopus database. Bibliometric analysis focuses on the metadata of journals, authors, and topics, visualized, and analyzed to produce a road map, research trends, and future agenda. The data were obtained from 207 articles published on Scopus downloaded on 29/8/2021 by using “shadow education” or “shadow curriculum” keywords. Furthermore, descriptive statistical methods and bibliometric analysis using Biblioshiny, an R-based application that generates bibliometric maps were used. Shadow education research has not been widely developed. Therefore, this bibliographic study may form the basis for future developments. Shadow education is the highest trend, followed by education and policy, high stakes testing, teacher education, curriculum, academic achievement, and private tutoring. This study provides an overview of trends in journals, authors, and research topics related to shadow education. Specifically, it provides relevant information to develop the potential and related themes in the future.